Konsep “High Quality Women” dalam Pernikahan: Definisi dan Persepsi Sosial - Endang Widiastuti; Margaretha Maria Shinta Pratiwi; Mulya Virgonita IW (EduInovasi: Journal of Basic Educational Studies, 2025)
This research analyzes the concept of "high quality women" in the Indonesian marriage context as a complex and multidimensional social phenomenon. The transformation of partner selection criteria from the traditional era to modernity reflects fundamental changes in contemporary marriage paradigms. Using a narrative literature review approach, this study explores the definition, social perception, and implications of this concept on relationship dynamics in Indonesian society. Findings indicate that the concept of "high quality women" encompasses academic achievement, financial stability, physical appearance, and personality that balances modern independence with traditional values. Digital media, particularly social media platforms, serves as the primary catalyst in constructing and disseminating standards of female ideality, while globalization influences introduce templates that are not always compatible with local culture. Significant impacts on partner selection dynamics include the emergence of "checklist mentality" and "relationship inflation" resulting in delayed relationship formation. Psychological implications show increased anxiety and perfectionism among women, with self-worth construction dependent on external validation. The negotiation process between modern concepts and traditional Indonesian values creates unique identity complexities requiring balance between personal aspirations and cultural expectations. This research provides important contributions to understanding the evolution of marriage standards and their impact on women's well-being in contemporary Indonesian society.